Relationship between attitude, knowledge, and support towards the acceptance of sustainable agriculture among contract farmers in Malaysia - Azman, Azmariana; Alby, Jeffrey Lawrence D'Silva; Abu Samah, Bahaman; Man, Norsida; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2013)
Sustainable agriculture practices are known as the best techniques by which to cultivate crops. To ensure the continuity of such practices, farmers should accept and apply this method on their yield. There is an abundance of international studies which have found that attitude, knowledge and support are the main factors to impinge on the acceptance of sustainable agriculture among farmers, but studies on the same scenario are lacking for Malaysia. Filling this research gap is the main objective of this study, which seeks to elucidate the relationship between attitude, knowledge and support towards the acceptance of sustainable agriculture among contract farmers in Malaysia. This is a quantitative study, and a total of 326 respondents were involved in the data collection process. The data were gained through a developed questionnaire. The resulting analysis proves that there is a significant relationship between contract farmers’ attitudes and their acceptance of sustainable agriculture (r=0.498, p=0.00). Contract farmers’ knowledge and their acceptance of sustainable agriculture are also shown to demonstrate a significant relationship (r= 0.348, 0.00). Additionally, there is support for a significant correlation between knowledge and acceptance of sustainable agriculture (r=0.365, p=0.00). In conclusion, farmers should have positive attitudes and adequate knowledge, and should obtain support from several parties to encourage them to embed sustainable agriculture within their farming practices.